How legal technology will change the business of law - VEITH, Christian (Institutional Knowledge at Singapore Management University, 2016)
Powerful forces are reshaping the corporate legal-advice market, including price pressurefrom clients and the digitization of legal data. Legal-technology solutions can help law firmssucceed in this new era, but only if they understand the tech landscape and redefine keyelements of their business model.Mapping the Legal-Tech LandscapeThe legal-tech landscape comprises three solution categories: enabler technologies facilitating the digitization of legal data, support-process solutions infusing new efficiencies intocase-management and back-office work, and substantive law solutions supporting or replacing lawyers in executing core legal tasks in transactions and litigation cases.Legal Tech’s Impact—Today and TomorrowWhile legal tech began with the automation of standard legal tasks, it’s moving towardsupporting more bespoke, specialized activities performed by lawyers. It’s also capitalizingon opportunities presented by big data analytics, helping lawyers capture valuable insightsfrom large data sets.Next Steps for Law FirmsTo safeguard their market share and profitability in a market transformed by legal tech, lawfirms must rethink two elements of their business model: their value proposition (includingtheir service offerings and revenue model) and their operating model (including their coststructure and organizational structure). The right decision for each element will differ for “biglaw” and “small law” firms that focus on standardized cases.Legal Tech’s Impact on Individual Roles and Legal EducationIn the future, the business of law will require fewer general support staff members, juniorlawyers, and generalists—and more legal technicians and project managers. Accordingly, lawschools may need to offer courses on legal tech and case-management processes. Law firmscan offer on-the-job training to help lawyers leverage legal-tech solutions and executive-education programs focused on legal-tech literacy.